Barbarian mine eaudiobook - Dixon, Ruby (Ice Planet Barbarians, 2018)
The ice planet has given me a second lease on life, so I'm thrilled to be here. Sure, there's no cheeseburgers, but I'm healthy and ready to be a productive member of the small tribe. What I didn't anticipate? That there'd be a savage stranger waiting nearby, watching me. And when he takes me captive, the unthinkable happens . . . I resonate to him. Resonance means mating, and children . . . but I don't know if this guy's ever been around anyone before. He's truly a barbarian in all ways, right down to clubbing me over the head and claiming me as his own. So why is it that I crave his touch and hunger for more? Contains mature themes.